Manganese-based positive electrode material with ordered-disordered two-phase structure

By introducing an ordered-disordered two-phase structure into the manganese-based positive electrode material and combining in-situ reaction synthesis technology, the problems of low capacity and short cycle life of manganese-based positive electrode material are solved, and specific capacity improvement and cycle performance improvement are achieved, which is suitable for industrial production.

CN119920894APending Publication Date: 2025-05-02UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410534673.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing manganese-based positive electrode materials have Jahn-Teller effect, Mn3+ disproportionation reaction and poor electrochemical activity, resulting in low capacity and severe attenuation of lithium manganese oxides, and poor reversibility of oxygen ion redox in disordered structures, resulting in low capacity retention and short cycle life.

Method used

The manganese-based positive electrode material with an ordered-disordered two-phase structure is directly synthesized through in-situ reaction, combining the high capacity of the ordered structure and the high capacity retention rate of the disordered structure to improve the specific capacity and cyclic performance of the material.

Benefits of technology

The specific capacity improvement and cycle performance improvement of manganese-based positive electrode materials is achieved, which reduces production costs, is suitable for large-scale industrial production, and overcomes the problems of low capacity retention and short cycle life of traditional manganese-based positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920894A_ABST
    Figure CN119920894A_ABST
Patent Text Reader

Abstract

The invention provides a manganese-based positive electrode material with an ordered-disordered two-phase structure, and belongs to the fields of lithium ion battery technology and electrochemistry. The manganese-based positive electrode material is a two-phase mixture of an ordered structure phase and a disordered rock salt structure phase, wherein the content of the ordered structure phase is not less than 5%; the manganese-based positive electrode material comprises a LiMnO2-based positive electrode material, a Li2MnO2-based positive electrode material, a Li2MnO3-based positive electrode material, a LiMn2O4-based positive electrode material and a LiMnPO4-based ordered-disordered two-phase positive electrode material. The manganese-based positive electrode material with an ordered-disordered two-phase structure is directly synthesized through an in-situ reaction, and the high capacity of an ordered structure and the high capacity retention rate of a disordered structure are combined, so that the specific capacity and the cycle performance of the manganese-based positive electrode material are favorably improved; meanwhile, the synthesis process is simple, raw materials are low in price, and the method is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion battery technology and electrochemistry, and in particular to a manganese-based positive electrode material with an ordered-disordered two-phase structure. Background Art

[0002] The rapid development of portable electronic products and electric vehicles has put forward higher requirements on the performance and price of energy storage systems. Lithium-ion batteries have the highest weight / volume energy density among current commercial batteries, and their development determines the performance level of the future battery market. In order to further improve the energy density and reduce the cost of lithium-ion batteries, the development of positive electrode materials is crucial. The currently widely used ternary positive electrode materials are prone to safety hazards, and the resources of nickel and cobalt are limited, which limits their further promotion from the perspective of cost-effectiveness. Low-cost lithium iron phosphate materials sacrifice electrode kinetics and energy density. This requires researchers to develop lithium-ion battery positive electrode materials with higher specific capacity, cycle stability and low cost.

[0003] Manganese-based cathode materials with low cost, high abundance and excellent thermal stability have become favorable candidates for cathode materials of the new generation of lithium-ion batteries. Its preparation process is simple and has great advantages in actual commercial production. These superior properties make it a more ideal cathode material.

[0004] However, the traditional ordered manganese-based cathode materials (including layered cathode materials based on LiMnO2, Li2MnO3 and Li2MnO2, spinel cathode materials based on LiMn2O4 and olivine cathode materials based on LiMnPO4) have Jahn-Teller effect, Mn 3+ Problems such as disproportionation reaction and poor electrochemical activity result in low capacity and severe attenuation of lithium manganese oxide.

[0005] In order to improve the capacity, in recent years, people have conducted a lot of research on different cation disordered structures (DRX) corresponding to different structures of manganese-based materials. They use the addition of excess Li to form 0-TM diffusion channels in pure disordered structures for energy storage, and provide additional active sites through oxygen ion redox, thereby improving the capacity of manganese-based positive electrode materials. However, the poor reversibility of oxygen ion redox makes the capacity retention rate of typical disordered manganese-based materials low and the cycle life short, which has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention provides a manganese-based positive electrode material with an ordered-disordered two-phase structure. The present invention directly synthesizes the manganese-based positive electrode material with an ordered-disordered two-phase structure through an in-situ reaction, combines the high capacity of the ordered structure with the high capacity retention rate of the disordered structure, and is conducive to improving the specific capacity and cycle performance of the manganese-based positive electrode material; at the same time, the present invention has a simple synthesis process, low raw material price, and is suitable for industrial large-scale production.

[0007] The technical solution of the present invention is as follows:

[0008] A manganese-based positive electrode material with an ordered-disordered two-phase structure, wherein the manganese-based positive electrode material is a two-phase mixture of an ordered structure phase and a disordered rock salt structure phase, wherein the content of the ordered structure phase is not less than 5%.

[0009] Preferably, the manganese-based positive electrode material is a LiMnO2-based ordered-disordered two-phase positive electrode material, whose molecular formula is Li 1+ x Mn y M z O 2-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤1, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0010] Preferably, the manganese-based positive electrode material is a Li2MnO2-based ordered-disordered two-phase positive electrode material, whose molecular formula is Li 2- x Mn y M z O 2-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0011] Preferably, the manganese-based positive electrode material is a Li2MnO3-based ordered-disordered two-phase positive electrode material, and its molecular formula is Li 2- x Mn y M z O 3-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0012] Preferably, the manganese-based positive electrode material is a LiMn2O4-based ordered-disordered two-phase positive electrode material, whose molecular formula is Li 1+ x Mn2-y M z O 4-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0<y≤1, 0<z≤0.9, 0≤q≤0.5.

[0013] Preferably, the manganese-based positive electrode material is a LiMnPO4-based ordered-disordered two-phase positive electrode material, whose molecular formula is Li 1+x Mn y M z PO 4-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0014] Furthermore, the metal cation represented by M includes but is not limited to Ni 2+ ,Co 3+ , Fe 3+ ,Cr 3+ , Al 3+ , Ga 3+ ,In 3+ , Ti 4+ , Sn 4+ , Zr 4+ , Nb 5+ , Mo 6+ One or more of.

[0015] Furthermore, the anion represented by N includes but is not limited to F - , N 3- , Cl - , S 2- One or more of.

[0016] The synthesis method of the manganese-based positive electrode material with an ordered-disordered two-phase structure described in the present invention includes but is not limited to a solid phase reaction method and a molten salt method. Of the two preparation processes, the solid phase reaction method has the advantages of low cost, large output and simple preparation process. The molten salt method has the advantages of relatively simple process, easy process control, low reaction temperature and low energy consumption. In this synthesis process, the compounds of Li and TM in the raw materials can be partially or completely dissolved in the molten salt, promoting the liquid nucleation / growth of the particles, and further reducing the sintering temperature and insulation time, effectively reducing energy consumption, and at the same time, submicron or nanometer particles can be obtained by the molten salt method.

[0017] The present invention explores how to prepare a manganese-based positive electrode material with an ordered-disordered two-phase structure from the perspective of the sintering process and the types of reactants. Through experiments, it is found that when the sintering temperature is too low, the sintering process is incomplete, and the reactants are not completely decomposed and residues appear. When the sintering temperature is too high, a two-phase structure cannot be obtained, and only an ordered structure or a single phase of a disordered structure can be obtained. In addition, the type of reactant also affects the preparation of a manganese-based positive electrode material with an ordered-disordered two-phase structure. When a reactant with high reactivity is selected, only a single phase of an ordered structure or a disordered structure can be obtained. When a reactant with low reactivity is selected, it is beneficial to prepare a manganese-based positive electrode material with an ordered-disordered two-phase structure.

[0018] In summary, the necessary condition for the solid phase reaction method to prepare the ordered-disordered two-phase structure of manganese-based positive electrode materials is that the sintering temperature range must be between 550-1150°C. The necessary condition for the molten salt method to prepare the ordered-disordered two-phase structure of manganese-based positive electrode materials is that the sintering temperature range must be between 450-1150°C, and the melting point of the selected salt compound is lower than the sintering temperature for preparing the positive electrode material. In addition, the reactants in the raw materials need to have low reactivity during the sintering process, such as Mn2O3, MnCO3, Li2O, and Li2CO3.

[0019] 1. For LiMnO2-based ordered-disordered two-phase positive electrode materials, the preparation method can be a solid phase reaction method or a molten salt method.

[0020] (I) The solid phase reaction method includes the following steps:

[0021] A1. Weigh the chemical formula Li according to the stoichiometric ratio 1+x Mn y M z O 2-q N q The Li compound, the Mn compound, the M compound and the N compound are fully mixed by a wet ball milling process, and then dried to obtain a precursor powder;

[0022] A2. Heat-treat the precursor powder, cool it to room temperature and take it out;

[0023] A3. Grind the product to obtain the target product powder, that is, obtain a manganese-based positive electrode material with an ordered-disordered two-phase structure.

[0024] Preferably, in step A1, for the molecular formula Li 1+x Mn y M z O 2-q N q , the contents of x, y, z and q are required to satisfy 0≤x≤1, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0025] Preferably, in step A1, the Mn compound includes but is not limited to one or more of Mn2CO3, Mn2O3, MnO(OH), Mn(OH)2, and manganese acetate;

[0026] The compound of Li includes, but is not limited to, one or more of LiOH·H2O, LiOH, Li2CO3, Li2O, lithium nitrate, lithium oxalate, and lithium acetate;

[0027] When N contains fluorine, F - The compound includes but is not limited to one or more of lithium fluoride, ammonium fluoride, and hydrogen fluoride;

[0028] When N contains nitrogen, N 3- The compounds include lithium nitride;

[0029] When N contains chlorine, Cl - The compound includes one or more of lithium chloride and ammonium chloride;

[0030] When N contains sulfur, S 2- The compound includes one or more of lithium sulfide and ammonium sulfide.

[0031] When M contains nickel, Ni 2+ The compound includes but is not limited to one or more of nickel carbonate, NiO, Ni2O3, nickel acetate, and nickel nitrate;

[0032] When M contains cobalt, Co 3+ The compound includes but is not limited to one or more of cobalt carbonate, Co2O3, Co3O4, CoO, cobalt acetate, and cobalt nitrate;

[0033] When M contains iron, Fe 3+ The compound includes but is not limited to one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, ferrous oxalate, ferrous acetate, and ferric nitrate;

[0034] When M contains chromium, Cr 3+ The compound includes but is not limited to one or more of Cr2O3, Cr(OH)3, CrO3, and chromium nitrate;

[0035] When M contains aluminum, Al 3+ The compound includes but is not limited to aluminum oxalate, one or more of Al2O3, Al(OH)3, aluminum acetate, aluminum oxalate, and aluminum nitrate;

[0036] When M contains gallium, Ga 3+ The compound includes but is not limited to one or more of Ga2O3, Ga(OH)3, and gallium nitrate;

[0037] When M contains indium, In3+ The compound includes but is not limited to one or more of In2O3, In(OH)3, and indium nitrate;

[0038] When M contains titanium, Ti 4+ The compound includes but is not limited to one or more of TiO2, titanium oxalate, and titanium nitrate;

[0039] When M contains tin, Sn 4+ The compound includes but is not limited to one or more of SnO, SnO2, Sn(OH)4, stannous oxalate, etc.;

[0040] When M contains zirconium, Zr 4+ The compound includes but is not limited to one or more of ZrO2, Zr(OH)4, and zirconium carbonate;

[0041] When M contains niobium, Nb 5+ The compound includes but is not limited to one or more of Nb2O5 and niobium hydroxide;

[0042] When M contains molybdenum, Mo 6+ The compounds include but are not limited to one or more of MoO3 and molybdenum hydroxide.

[0043] Preferably, in step A2, the heat treatment is carried out at 550-1150° C. for 3-12 hours in an argon atmosphere.

[0044] (ii) The molten salt method includes the following steps:

[0045] B1. Weigh the chemical formula Li according to the stoichiometric ratio 1+x Mn y M z O 2-q N q The Li compound, the Mn compound, the M compound, the N compound and the salt compound are fully mixed by a wet ball milling process, and then dried to obtain a precursor powder;

[0046] B2. Heat-treating the precursor powder, cooling it to room temperature and taking it out;

[0047] B3, dissolving the heat-treated product with a solvent that removes easily soluble salts by ultrasonic vibration, washing it multiple times, and then filtering and drying it to obtain a material with an ordered-disordered two-phase structure;

[0048] Preferably, in step B1, the compound selected from the salt includes but is not limited to one or more of lithium chloride, lithium sulfate, lithium carbonate, lithium nitrate, potassium chloride, potassium sulfate, potassium carbonate, potassium nitrate, sodium chloride, sodium sulfate, sodium carbonate, and sodium nitrate.

[0049] Preferably, in step B1, for the molecular formula Li 1+x Mn y M z O 2-q N q , the contents of x, y, z and q are required to be consistent with A1.

[0050] Preferably, in step B1, the mass ratio of the total mass of the Li compound and the Mn compound to the mass ratio of the salt compound is 1:(1-10).

[0051] Preferably, in step B1, when two or more salt compounds are selected, the molar ratio of the salt compounds is arbitrary.

[0052] More preferably, in step B1, the lowest eutectic point of the selected salt compound needs to be lower than the sintering temperature during heat treatment.

[0053] Preferably, in step B1, the Mn compound includes, in addition to A1, one or more of manganese sulfate, manganese nitrate, and manganese chloride;

[0054] The compound of Li is the same as A1; the compound of N is the same as A1.

[0055] When M contains nickel, Ni 2+ The compound includes, in addition to A1, one or more of nickel chloride and nickel sulfate;

[0056] When M contains cobalt, Co 3+ The compound includes, in addition to A1, one or more of cobalt chloride and cobalt sulfate;

[0057] When M contains iron, Fe 3+ The compound includes, in addition to A1, one or more of ferric chloride and ferric sulfate;

[0058] When M contains chromium, Cr 3+ The compound includes, in addition to A1, one or more of chromium sulfate and CrCl3;

[0059] When M contains aluminum, Al 3+ The compound includes, in addition to A1, one or more of aluminum chloride and aluminum sulfate;

[0060] When M contains gallium, Ga 3+ The compound includes, in addition to A1, one or more of gallium chloride and gallium sulfate;

[0061] When M contains indium, In 3+ The compound includes, in addition to A1, one or more of indium chloride and indium sulfate;

[0062] When M contains titanium, Ti 4+ The compound includes, in addition to A1, one or more of TiCl3, TiCl4, and titanium sulfate;

[0063] When M contains tin, Sn 4+ The compound includes, in addition to A1, one or more of stannous chloride and stannous sulfate;

[0064] When M contains zirconium, Zr 4+ The compound includes, in addition to A1, one or more of zirconium chloride and zirconium sulfate;

[0065] When M contains niobium, Nb 5+ The compound includes, in addition to A1, one or more of niobium chloride, but is not limited thereto;

[0066] When M contains molybdenum, Mo 6+ The compound contains, in addition to A1, one or more of molybdenum chlorides, but is not limited to them.

[0067] Preferably, in step B2, the heat treatment is carried out at 450-1150° C. for 3-12 hours in an argon atmosphere.

[0068] Preferably, in step B3, the solvent that easily dissolves the salt includes one of deionized water, anhydrous ethanol or acetone.

[0069] (III) In the above preparation process, preferably, in steps A1 and B1, when wet ball milling is performed, the grinding aid includes one of anhydrous ethanol, ethylene glycol, propylene glycol or isopropanol.

[0070] More preferably, in steps A1 and B1, the wet ball milling process is as follows: the material, balls and grinding aid are placed in a ball milling jar in a mass ratio of 1:(1-2):(2-4), which is then sealed and placed on a ball mill for ball milling at a speed of 300-1400 r / min for 1-10 h.

[0071] Preferably, in steps A1 and B1, the drying temperature and the drying time are 60-100° C. and 12-24 h, respectively.

[0072] Preferably, in steps A1 and B1, the average particle size of the precursor powder is 100-200 nm.

[0073] 2. For Li2MnO2-based ordered-disordered two-phase positive electrode materials, the preparation method can be a solid phase reaction method or a molten salt method.

[0074] (I) The solid phase reaction method includes the following steps:

[0075] C1. Weigh the chemical formula Li according to the stoichiometric ratio 2-x Mn y M z O 2-q N q The Li compound, the Mn compound, the M compound and the N compound are fully mixed by a wet ball milling process, and then dried to obtain a precursor powder;

[0076] C2, heat-treating the precursor powder, cooling it to room temperature and taking it out;

[0077] C3. Grind the product to obtain the target product powder, that is, obtain a manganese-based positive electrode material with an ordered-disordered two-phase structure.

[0078] Preferably, in step C1, for the molecular formula Li 2-x Mn y M z O 2-q N q , the contents of x, y, z and q are required to satisfy 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0079] Preferably, in step C1, the Mn compound includes but is not limited to one or more of Mn2CO3, Mn2O3, MnO(OH), Mn(OH)2, and manganese acetate;

[0080] The compound of Li includes, but is not limited to, one or more of LiOH·H2O, LiOH, Li2CO3, Li2O, lithium nitrate, lithium oxalate, and lithium acetate;

[0081] When N contains fluorine, F - The compound includes but is not limited to one or more of lithium fluoride, ammonium fluoride, and hydrogen fluoride;

[0082] When N contains nitrogen, N 3- The compounds include lithium nitride;

[0083] When N contains chlorine, Cl - The compound includes one or more of lithium chloride and ammonium chloride;

[0084] When N contains sulfur, S 2- The compound includes one or more of lithium sulfide and ammonium sulfide.

[0085] When M contains nickel, Ni 2+ The compound includes but is not limited to one or more of nickel carbonate, NiO, Ni2O3, nickel acetate, and nickel nitrate;

[0086] When M contains cobalt, Co3+ The compound includes but is not limited to one or more of cobalt carbonate, Co2O3, Co3O4, CoO, cobalt acetate, and cobalt nitrate;

[0087] When M contains iron, Fe 3+ The compound includes but is not limited to one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, ferrous oxalate, ferrous acetate, and ferric nitrate;

[0088] When M contains chromium, Cr 3+ The compound includes but is not limited to one or more of Cr2O3, Cr(OH)3, CrO3, and chromium nitrate;

[0089] When M contains aluminum, Al 3+ The compound includes but is not limited to aluminum oxalate, one or more of Al2O3, Al(OH)3, aluminum acetate, aluminum oxalate, and aluminum nitrate;

[0090] When M contains gallium, Ga 3+ The compound includes but is not limited to one or more of Ga2O3, Ga(OH)3, and gallium nitrate;

[0091] When M contains indium, In 3+ The compound includes but is not limited to one or more of In2O3, In(OH)3, and indium nitrate;

[0092] When M contains titanium, Ti 4+ The compound includes but is not limited to one or more of TiO2, titanium oxalate, and titanium nitrate;

[0093] When M contains tin, Sn 4+ The compound includes but is not limited to one or more of SnO, SnO2, Sn(OH)4, stannous oxalate, etc.;

[0094] When M contains zirconium, Zr 4+ The compound includes but is not limited to one or more of ZrO2, Zr(OH)4, and zirconium carbonate;

[0095] When M contains niobium, Nb 5+ The compound includes but is not limited to one or more of Nb2O5 and niobium hydroxide;

[0096] When M contains molybdenum, Mo 6+ The compounds include but are not limited to one or more of MoO3 and molybdenum hydroxide.

[0097] Preferably, in step C2, the heat treatment is carried out at 550-1150° C. for 3-12 hours in an argon atmosphere.

[0098] (ii) The molten salt method includes the following steps:

[0099] D1. Weigh the chemical formula Li according to the stoichiometric ratio 2-x Mn y M z O 2-q N q The Li compound, the Mn compound, the M compound, the N compound and the salt compound are fully mixed by a wet ball milling process, and then dried to obtain a precursor powder;

[0100] D2, heat-treating the precursor powder, cooling it to room temperature and taking it out;

[0101] D3. The product after heat treatment is dissolved by ultrasonic vibration using a solvent that removes easily soluble salts, washed multiple times, and then filtered and dried to obtain a material with an ordered-disordered two-phase structure;

[0102] Preferably, in step D1, the compound selected from the salt includes but is not limited to one or more of lithium chloride, lithium sulfate, lithium carbonate, lithium nitrate, potassium chloride, potassium sulfate, potassium carbonate, potassium nitrate, sodium chloride, sodium sulfate, sodium carbonate, and sodium nitrate.

[0103] Preferably, in step D1, for the molecular formula Li 2-x Mn y M z O 2-q N q , the contents of x, y, z and q are required to be consistent with A1.

[0104] Preferably, in step D1, the mass ratio of the total mass of the Li compound and the Mn compound to the mass ratio of the salt compound is 1:(1-10).

[0105] Preferably, in step D1, when two or more salt compounds are selected, the molar ratio of the salt compounds is arbitrary.

[0106] More preferably, in step D1, the lowest eutectic point of the selected salt compound needs to be lower than the sintering temperature during heat treatment.

[0107] Preferably, in step D1, the Mn compound includes, in addition to C1, one or more of manganese sulfate, manganese nitrate, and manganese chloride;

[0108] The compound of Li is consistent with C1; the compound of N is consistent with C1.

[0109] When M contains nickel, Ni 2+ The compound includes, in addition to C1, one or more of nickel chloride and nickel sulfate;

[0110] When M contains cobalt, Co 3+ The compound includes, in addition to C1, one or more of cobalt chloride and cobalt sulfate;

[0111] When M contains iron, Fe 3+ The compound includes, in addition to C1, one or more of ferric chloride and ferric sulfate;

[0112] When M contains chromium, Cr 3+ The compound includes, in addition to Cl, one or more of chromium sulfate and CrCl3;

[0113] When M contains aluminum, Al 3+ The compound includes, in addition to C1, one or more of aluminum chloride and aluminum sulfate;

[0114] When M contains gallium, Ga 3+ The compound includes, in addition to C1, one or more of gallium chloride and gallium sulfate;

[0115] When M contains indium, In 3+ The compound includes C1, and also includes but is not limited to one or more of indium chloride and indium sulfate;

[0116] When M contains titanium, Ti 4+ The compound includes, in addition to Cl, one or more of TiCl3, TiCl4, and titanium sulfate;

[0117] When M contains tin, Sn 4+ The compound includes, in addition to C1, one or more of stannous chloride and stannous sulfate;

[0118] When M contains zirconium, Zr 4+ The compound includes, in addition to Cl, one or more of zirconium chloride and zirconium sulfate, but is not limited thereto;

[0119] When M contains niobium, Nb 5+ The compound includes, in addition to C1, one or more of niobium chloride, but is not limited thereto;

[0120] When M contains molybdenum, Mo 6+ The compound includes, in addition to Cl, one or more of molybdenum chlorides, but is not limited to.

[0121] Preferably, in step D2, the heat treatment is carried out at 450-1150° C. for 3-12 hours in an argon atmosphere.

[0122] Preferably, in step D3, the solvent that easily dissolves the salt includes one of deionized water, anhydrous ethanol or acetone.

[0123] (III) In the above preparation process, preferably, in steps C1 and D1, when wet ball milling is performed, the grinding aid includes one of anhydrous ethanol, ethylene glycol, propylene glycol or isopropanol.

[0124] More preferably, in steps C1 and D1, the wet ball milling process is as follows: the material, balls and grinding aid are placed in a ball milling jar in a mass ratio of 1:(1-2):(2-4), which is then sealed and placed on a ball mill for ball milling at a speed of 300-1400 r / min for 1-10 h.

[0125] Preferably, in steps C1 and D1, the drying temperature and the drying time are 60-100° C. and 12-24 h, respectively.

[0126] Preferably, in steps C1 and D1, the average particle size of the precursor powder is 100-200 nm.

[0127] 3. For Li2MnO3-based ordered-disordered two-phase positive electrode materials, the preparation method can be a solid phase reaction method or a molten salt method.

[0128] (I) The solid phase reaction method includes the following steps:

[0129] E1. Weigh the chemical formula Li according to the stoichiometric ratio 2-x Mn y M z O 3-q N q The Li compound, the Mn compound and the M compound are fully mixed by a wet ball milling process, and then dried to obtain a precursor powder;

[0130] E2, heat-treating the precursor powder, cooling it to room temperature and taking it out;

[0131] E3. Grind the product to obtain the target product powder, that is, obtain a manganese-based positive electrode material with an ordered-disordered two-phase structure.

[0132] Preferably, in step E1, for the chemical formula Li 2-x Mn y M z O 3-q N q , the contents of x, y, z and q are required to satisfy 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0133] Preferably, in step E1, the Mn compound includes but is not limited to one or more of Mn2CO3, Mn2O3, MnO(OH), Mn(OH)2, and manganese acetate;

[0134] The compound of Li includes, but is not limited to, one or more of LiOH·H2O, LiOH, Li2CO3, Li2O, lithium nitrate, lithium oxalate, and lithium acetate;

[0135] When N contains fluorine, F - The compound includes but is not limited to one or more of lithium fluoride, ammonium fluoride, and hydrogen fluoride;

[0136] When N contains nitrogen, N 3- The compounds include lithium nitride;

[0137] When N contains chlorine, Cl - The compound includes one or more of lithium chloride and ammonium chloride;

[0138] When N contains sulfur, S 2- The compound includes one or more of lithium sulfide and ammonium sulfide.

[0139] When M contains nickel, Ni 2+ The compound includes but is not limited to one or more of nickel carbonate, NiO, Ni2O3, nickel acetate, and nickel nitrate;

[0140] When M contains cobalt, Co 3+ The compound includes but is not limited to one or more of cobalt carbonate, Co2O3, Co3O4, CoO, cobalt acetate, and cobalt nitrate;

[0141] When M contains iron, Fe 3+ The compound includes but is not limited to one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, ferrous oxalate, ferrous acetate, and ferric nitrate;

[0142] When M contains chromium, Cr 3+ The compound includes but is not limited to one or more of Cr2O3, Cr(OH)3, CrO3, and chromium nitrate;

[0143] When M contains aluminum, Al 3+ The compound includes but is not limited to aluminum oxalate, one or more of Al2O3, Al(OH)3, aluminum acetate, aluminum oxalate, and aluminum nitrate;

[0144] When M contains gallium, Ga 3+ The compound includes but is not limited to one or more of Ga2O3, Ga(OH)3, and gallium nitrate;

[0145] When M contains indium, In 3+ The compound includes but is not limited to one or more of In2O3, In(OH)3, and indium nitrate;

[0146] When M contains titanium, Ti4+ The compound includes but is not limited to one or more of TiO2, titanium oxalate, and titanium nitrate;

[0147] When M contains tin, Sn 4+ The compound includes but is not limited to one or more of SnO, SnO2, Sn(OH)4, stannous oxalate, etc.;

[0148] When M contains zirconium, Zr 4+ The compound includes but is not limited to one or more of ZrO2, Zr(OH)4, and zirconium carbonate;

[0149] When M contains niobium, Nb 5+ The compound includes but is not limited to one or more of Nb2O5 and niobium hydroxide;

[0150] When M contains molybdenum, Mo 6+ The compounds include but are not limited to one or more of MoO3 and molybdenum hydroxide.

[0151] In the above preparation process, preferably, in step E1, when wet ball milling is performed, the grinding aid includes one of anhydrous ethanol, ethylene glycol, propylene glycol or isopropanol.

[0152] More preferably, in step E1, the wet ball milling process is as follows: the material, balls and grinding aid are placed in a ball milling jar in a mass ratio of 1:(1-2):(2-4), which is then sealed and placed on a ball mill for ball milling at a speed of 300-1400 r / min for 1-10 h.

[0153] Preferably, in step E1, the drying temperature and the drying time are 60-100° C. and 12-24 h, respectively.

[0154] Preferably, in step E1, the average particle size of the precursor powder is 100-200 nm.

[0155] Preferably, in step E2, the heat treatment is carried out at 550-1150° C. for 3-12 hours in an argon atmosphere.

[0156] (ii) For the molten salt method, it is similar to steps D1, D2, and D3.

[0157] Preferably, for the chemical formula Li 2-x Mn y M z O 3-q N q , requiring that the contents of x, y, z and q are similar to those of E1.

[0158] 4. For the LiMn2O4-based ordered-disordered two-phase positive electrode material, its preparation method can be a solid phase reaction method or a molten salt method.

[0159] (I) The molten salt method includes the following steps:

[0160] F1. Weigh the chemical formula Li according to the stoichiometric ratio 1+x Mn 2-y M z O 4-q N q The Li compound, the Mn compound, the M compound, the N compound and the salt compound are fully mixed by a wet ball milling process, and then dried to obtain a precursor powder;

[0161] F2, heat-treating the precursor powder, cooling it to room temperature and taking it out;

[0162] F3. The product after heat treatment is dissolved by ultrasonic vibration using a solvent that removes easily soluble salts, washed multiple times, and then filtered and dried to obtain a material with an ordered-disordered two-phase structure;

[0163] Preferably, in step F1, for the chemical formula Li 1+x Mn 2-y M z O 4-q N q , the contents of x, y, z and q are required to satisfy 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0164] Preferably, in step F1, the Mn compound includes but is not limited to one or more of Mn2CO3, Mn2O3, MnO(OH), Mn(OH)2, manganese sulfate, manganese acetate, manganese nitrate, and manganese chloride;

[0165] The compound of Li includes, but is not limited to, one or more of LiOH·H2O, LiOH, Li2CO3, Li2O, lithium nitrate, lithium oxalate, and lithium acetate;

[0166] When N contains fluorine, F - The compound includes but is not limited to one or more of lithium fluoride, ammonium fluoride, and hydrogen fluoride;

[0167] When N contains nitrogen, N 3- The compounds include lithium nitride;

[0168] When N contains chlorine, Cl - The compound includes one or more of lithium chloride and ammonium chloride;

[0169] When N contains sulfur, S 2- The compound includes one or more of lithium sulfide and ammonium sulfide.

[0170] When M contains nickel, Ni 2+ The compound includes but is not limited to one or more of nickel carbonate, NiO, Ni2O3, nickel acetate, nickel nitrate, nickel chloride, and nickel sulfate;

[0171] When M contains cobalt, Co 3+ The compound includes but is not limited to one or more of cobalt carbonate, Co2O3, Co3O4, CoO, cobalt acetate, cobalt nitrate, cobalt chloride, and cobalt sulfate;

[0172] When M contains iron, Fe 3+ The compound includes but is not limited to one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, ferrous oxalate, ferric acetate, ferric nitrate, ferric chloride, and ferric sulfate;

[0173] When M contains chromium, Cr 3+ The compound includes but is not limited to one or more of Cr2O3, Cr(OH)3, CrO3, chromium sulfate, chromium nitrate, and CrCl3;

[0174] When M contains aluminum, Al 3+ The compound includes but is not limited to aluminum oxalate, one or more of Al2O3, Al(OH)3, aluminum acetate, aluminum nitrate, aluminum sulfate, and aluminum oxalate;

[0175] When M contains gallium, Ga 3+ The compound includes but is not limited to one or more of Ga2O3, Ga(OH)3, gallium chloride, gallium nitrate, and gallium sulfate;

[0176] When M contains indium, In 3+ The compound includes but is not limited to one or more of In2O3, In(OH)3, indium chloride, indium nitrate, and indium sulfate;

[0177] When M contains titanium, Ti 4+ The compound includes but is not limited to one or more of TiO2, TiCl3, TiCl4, titanium oxalate, titanium nitrate, and titanium sulfate;

[0178] When M contains tin, Sn 4+ The compound includes but is not limited to one or more of SnO, SnO2, Sn(OH)4, stannous chloride, stannous oxalate, and stannous sulfate;

[0179] When M contains zirconium, Zr 4+ The compound includes but is not limited to one or more of ZrO2, Zr(OH)4, zirconium chloride, zirconium carbonate, and zirconium sulfate;

[0180] When M contains niobium, Nb 5+The compound includes but is not limited to one or more of Nb2O5, niobium hydroxide, and niobium chloride;

[0181] When M contains molybdenum, Mo 6+ The compounds include but are not limited to one or more of MoO3, molybdenum hydroxide, and molybdenum chloride.

[0182] Preferably, in step F1, the compound selected from the salt includes but is not limited to one or more of lithium chloride, lithium sulfate, lithium carbonate, lithium nitrate, potassium chloride, potassium sulfate, potassium carbonate, potassium nitrate, sodium chloride, sodium sulfate, sodium carbonate, and sodium nitrate.

[0183] Preferably, in step F1, the mass ratio of the total mass of the Li compound and the Mn compound to the mass ratio of the salt compound is 1:(1-10).

[0184] Preferably, in step F1, when two or more salt compounds are selected, the molar ratio of the salt compounds is arbitrary.

[0185] More preferably, in step F1, the lowest eutectic point of the selected salt compound needs to be lower than the sintering temperature during heat treatment.

[0186] Preferably, in step F2, the heat treatment is calcination at 450-1150° C. for 3-12 h in an argon atmosphere.

[0187] Preferably, in step F3, the solvent that easily dissolves the salt includes one of deionized water, anhydrous ethanol or acetone.

[0188] (ii) For the solid phase reaction method, it is similar to steps C1, C2, and C3.

[0189] 5. For the LiMnPO4-based ordered-disordered two-phase positive electrode material, the preparation method can be a solid phase reaction method or a molten salt method.

[0190] (I) The solid phase reaction method includes the following steps:

[0191] G1. Weigh the chemical formula Li according to the stoichiometric ratio 1+x Mn y M z PO 4-q N q The Li compound, the Mn compound, the M compound and the N compound are fully mixed by a wet ball milling process, and then dried to obtain a precursor powder;

[0192] G2, heat-treating the precursor powder, cooling it to room temperature and taking it out;

[0193] G3. Grind the product to obtain the target product powder, that is, obtain a manganese-based positive electrode material with an ordered-disordered two-phase structure.

[0194] Preferably, in step G1, for the chemical formula Li 1+x Mn y M z PO 4-q N q , the contents of x, y, z and q are required to satisfy 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.5.

[0195] Preferably, in step E1, the Mn compound includes but is not limited to one or more of Mn2CO3, Mn2O3, MnO(OH), Mn(OH)2, and manganese acetate;

[0196] The compound of Li includes, but is not limited to, one or more of LiOH·H2O, LiOH, Li2CO3, Li2O, lithium nitrate, lithium oxalate, and lithium acetate;

[0197] When N contains fluorine, F - The compound includes but is not limited to one or more of lithium fluoride, ammonium fluoride, and hydrogen fluoride;

[0198] When N contains nitrogen, N 3- The compounds include lithium nitride;

[0199] When N contains chlorine, Cl - The compound includes one or more of lithium chloride and ammonium chloride;

[0200] When N contains sulfur, S 2- The compound includes one or more of lithium sulfide and ammonium sulfide;

[0201] When M contains nickel, Ni 2+ The compound includes but is not limited to one or more of nickel carbonate, NiO, Ni2O3, nickel acetate, and nickel nitrate;

[0202] When M contains cobalt, Co 3+ The compound includes but is not limited to one or more of cobalt carbonate, Co2O3, Co3O4, CoO, cobalt acetate, and cobalt nitrate;

[0203] When M contains iron, Fe 3+ The compound includes but is not limited to one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, ferrous oxalate, ferrous acetate, and ferric nitrate;

[0204] When M contains chromium, Cr 3+The compound includes but is not limited to one or more of Cr2O3, Cr(OH)3, CrO3, and chromium nitrate;

[0205] When M contains aluminum, Al 3+ The compound includes but is not limited to aluminum oxalate, one or more of Al2O3, Al(OH)3, aluminum acetate, aluminum oxalate, and aluminum nitrate;

[0206] When M contains gallium, Ga 3+ The compound includes but is not limited to one or more of Ga2O3, Ga(OH)3, and gallium nitrate;

[0207] When M contains indium, In 3+ The compound includes but is not limited to one or more of In2O3, In(OH)3, and indium nitrate;

[0208] When M contains titanium, Ti 4+ The compound includes but is not limited to one or more of TiO2, titanium oxalate, and titanium nitrate;

[0209] When M contains tin, Sn 4+ The compound includes but is not limited to one or more of SnO, SnO2, Sn(OH)4, stannous oxalate, etc.;

[0210] When M contains zirconium, Zr 4+ The compound includes but is not limited to one or more of ZrO2, Zr(OH)4, and zirconium carbonate;

[0211] When M contains niobium, Nb 5+ The compound includes but is not limited to one or more of Nb2O5 and niobium hydroxide;

[0212] When M contains molybdenum, Mo 6+ The compounds include but are not limited to one or more of MoO3 and molybdenum hydroxide.

[0213] In the above preparation process, preferably, in step G1, when wet ball milling is performed, the grinding aid includes one of anhydrous ethanol, ethylene glycol, propylene glycol or isopropanol.

[0214] More preferably, in step G1, the wet ball milling process is as follows: the material, balls and grinding aid are placed in a ball milling jar in a mass ratio of 1:(1-2):(2-4), which is then sealed and placed on a ball mill for ball milling at a speed of 300-1400 r / min for 1-10 h.

[0215] Preferably, in step G1, the drying temperature and drying time are 60-100° C. and 12-24 h, respectively.

[0216] Preferably, in step G1, the average particle size of the precursor powder is 100-200 nm.

[0217] Preferably, in step G2, the heat treatment is carried out at 550-1150° C. for 3-12 hours in an argon atmosphere.

[0218] (ii) For the molten salt method, it is similar to steps D1, D2, and D3.

[0219] Preferably, for the chemical formula Li 1+x Mn y M z PO 4-q N q , the contents of x, y, z and q are required to be consistent with G1.

[0220] The beneficial technical effects of the present invention are:

[0221] 1. The present invention introduces metal cations into lithium manganese oxide and adopts a simple preparation process to directly synthesize in situ a lithium manganese oxide two-phase positive electrode material in which an ordered structure and a disordered rock salt structure coexist. The ordered phase in the material can provide a lithium ion diffusion channel, so that energy storage can be performed without the need for an excess of Li 0-TM channel, reducing the dependence on excess lithium addition and anion redox, thereby improving the capacity retention rate of the positive electrode material.

[0222] 2. Taking the manganese-based positive electrode material LiMnO2 as an example, the chemical formula is Li 1+x Mn y M z O 2-q N q The manganese-based positive electrode material is composed of two phases, namely LiMnO2 with an ordered layered structure and DRX with a disordered rock salt structure. The ordered layered structure belongs to the Pmnm space group, and its Li ion layer, metal ion layer (Mn and M), and anion layer (O and N) are arranged alternately in an orderly manner. The disordered rock salt structure belongs to the Fm-3m space group, and the Li ion layer and metal ion layer (Mn and M) are partially or completely disordered.

[0223] 3. The composite positive electrode material of ordered structure and disordered rock salt structure synthesized in situ can greatly alleviate the problem of low capacity retention rate caused by Jahn-Teller effect in traditional manganese-based ordered structure positive electrode materials, and can also improve the problem of low capacity retention rate caused by oxygen ion redox effect in typical disordered manganese-based positive electrode materials. At the same time, the conductivity of the positive electrode material can also be improved by doping a small amount of metal oxide. In addition, the elemental composition of the ordered structure and the disordered rock salt structure is consistent, which makes the manganese-based positive electrode material with ordered-disordered two-phase structure have good compatibility.

[0224] 4. The cathode material prepared by the present invention can be used for lithium-ion batteries with high energy density, long cycle life, low toxicity and low price, overcoming the problem of low cycle life of existing manganese-based cathode materials with disordered cation structures, improving the preparation process of cathode materials of current lithium-ion batteries, increasing the capacity and capacity retention rate of ordered manganese-based cathode materials, and reducing the cost of cathode materials. At the same time, the cathode material of the present invention has high resource richness, is environmentally friendly, and is suitable for large-scale production and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0225] Figure 1 XRD pattern of the material synthesized in Example 1;

[0226] Figure 2 This is a SEM image of the material synthesized in Example 1;

[0227] Figure 3 The voltage cycle curve of the material synthesized in Example 1 in the voltage range of 1.6-4.8V;

[0228] Figure 4 The material synthesized in Example 1 has a voltage range of 1.6-4.8 V and a current density of 20 mA g -1 , 200mA g -1 Cycle performance diagram of

[0229] Figure 5 XRD pattern of the material synthesized in Example 2;

[0230] Figure 6 This is the XRD pattern of the material synthesized in Example 3. DETAILED DESCRIPTION

[0231] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0232] Example 1: Preparation of LiMnO2-type two-phase manganese-based positive electrode material by solid phase reaction method

[0233] Step 1: LiMn 0.8 Fe 0.1 Ti 0.1 Preparation of O2 two-phase structure cathode material

[0234] A1. Weigh 6.3152 g Mn2O3, 0.7987 g nano-TiO2, 0.7985 g nano-Fe2O3 and 3.8792 g Li2CO3 respectively, wherein the content of Li2CO3 added is an additional 5 wt% on the basis of the stoichiometric ratio to compensate for the loss of Li during the preparation process.

[0235] After the above ingredients are prepared, 11.7916g of the prepared powder, 20g of stainless steel balls prepared according to the particle size and 30ml of anhydrous ethanol are poured into a ball mill with a capacity of 80mm in sequence, and the ball mill is placed and fixed on the ball mill for mixing. The ball mill is milled at a speed of 1400r / min on the ball mill for 1h. The mixed slurry is placed in a beaker and dried at 70°C for 12h. The dried powder is ground with an agate mortar and sieved with a 200nm sieve to obtain a precursor powder with an average particle size of 100-200nm.

[0236] A2. Pour the dried powder into a corundum crucible and place it in a vacuum tube furnace. Heat treat it at 650°C in an argon atmosphere for 12 hours. The sample is cooled along with the furnace.

[0237] A3, take it out and pour it into an agate mortar to crush it to get LiMn 0.8 Fe 0.1 Ti 0.1 O2 two-phase cathode material.

[0238] Figure 1 LiMn 0.8 Fe 0.1 Ti 0.1 X-ray diffraction pattern (XRD) of O2 two-phase positive electrode material. The diffraction peaks in the figure show that the prepared products are o-LiMnO2 and DRX phases. Figure 2 The figure is a schematic diagram of a scanning electron microscope (SEM) of a two-phase material. The Fullprof software tool is used to refine and quantitatively analyze the composition content, and the ratio of the ordered structure to the disordered structure is calculated, wherein the content of the ordered structure is 72.3% and the content of the disordered structure is 27.7%.

[0239] When preparing Mn-based positive electrode materials, as the sintering temperature increases, the products will undergo transformations into m-LiMnO2, o-LiMnO2, and DRX in sequence. Compared with o-LiMnO2, m-LiMnO2 transforms from a layered structure to a spinel structure faster during the electrochemical cycle, resulting in more severe capacity decay. By changing the sintering system, a manganese-based ordered-disordered two-phase structure positive electrode material composed of o-LiMnO2 and DRX can be obtained. At the same time, the ratio of the two phases can also be adjusted by adjusting the sintering system to obtain a higher specific capacity and better capacity retention rate.

[0240] Step 2: Assembling a lithium-ion battery based on a manganese-based ordered-disordered two-phase structure cathode material

[0241] M1. Fully mix 280 mg of the product obtained in step 1, 80 mg of conductive carbon black Super P and 800 mg of a 5 wt% polyvinylidene fluoride solution. The 5 wt% polyvinylidene fluoride solution is prepared by fully mixing polyvinylidene fluoride with a solvent, N-methylpyrrolidone, by magnetic stirring.

[0242] M2. The mixed slurry is coated on aluminum foil, dried in a vacuum oven at 80°C, and the dried product is cut by a cutting machine to obtain the positive electrode material.

[0243] M3. Assemble a manganese-based ordered-disordered two-phase battery in a glove box filled with argon atmosphere, using a CR2032 button battery case, the positive electrode is the positive electrode material prepared in step M2, the electrolyte is LB-001 (1.0M LiPF6in EC:DMC=1:1Vol%), the separator is a polypropylene film (Celgard 2400), and the negative electrode is a lithium sheet.

[0244] M4. Assemble the negative electrode shell, lithium sheet, diaphragm, positive electrode, gasket, shrapnel and positive electrode shell in order, and press the above components into one in a button battery sealing machine to obtain a new manganese-based ordered-disordered two-phase battery.

[0245] Step 3: Testing of lithium-ion batteries based on manganese-based ordered-disordered two-phase structure cathode materials

[0246] N1. The charge-discharge cycle performance of the assembled manganese-based ordered-disordered two-phase battery was tested using the Xinwei battery testing system (BTS Client 8.0.0.471). The test conditions were a current density of 20 mA g -1 , 200mA g -1 , voltage range is 1.6-4.8V, temperature is room temperature 25℃. Test results are as follows Figure 3 , 4 As shown. At a current density of 20 mA g -1 The specific capacity is 174 mAh g at 20th -1 , at 100th, 158mAh g -1 , the capacity retention rate is 90.8%.

[0247] N2, as a comparison, the positive electrode material is replaced with olivine-type LiMn 0.8 Fe 0.1 Ti 0.1 The preparation process of O2 ordered layered single structure material is consistent with step 2 and step 3 of Example 1. The test results are: the current density is 20mAg-1 The specific capacity is 164 mAh g at 20th -1 , 132mAh g at 100th -1 , the capacity retention rate is 80.5%.

[0248] N3, as a comparison, the positive electrode material is replaced with ordinary LiMn 0.8 Fe 0.1 Ti 0.1 The preparation process of the O2 disordered rock salt single structure material is consistent with step 2 and step 3 of Example 1. The test results are: the current density is 20mA g -1 The specific capacity is 20 mAh g at 20th -1 , at 100th 18mAh g -1 , the capacity retention rate is 90.0%.

[0249] Example 2: Preparation of LiMnO2-type two-phase manganese-based positive electrode material by solid phase reaction method

[0250] Step 1: LiMn 0.8 Fe 0.1 Zr 0.1 Preparation of O2 two-phase structure cathode material

[0251] A1. Weigh 3.1576 g Mn2O3, 0.6161 g nano ZrO2, 0.3992 g nano Fe2O3 and 1.9396 g Li2CO3 respectively, wherein the content of Li2CO3 added is an additional 5 wt% on the basis of the stoichiometric ratio to compensate for the loss of Li during the preparation process.

[0252] After the above ingredients are prepared, 6.1125g of the prepared powder, 15g of stainless steel balls prepared according to the particle size and 20ml of ethylene glycol are poured into a ball mill with a capacity of 80mm in sequence, and the ball mill is placed and fixed on the ball mill for mixing. The ball mill is milled at a speed of 700r / min on the ball mill for 3h. The mixed slurry is placed in a beaker and dried at 60°C for 24h. The dried powder is ground with an agate mortar and sieved with a 200nm sieve to obtain a precursor powder with an average particle size of 100-200nm.

[0253] A2. Pour the dried powder into a corundum crucible and place it in a vacuum tube furnace. Heat treat it at 750°C in an argon atmosphere for 6 hours. The sample is cooled with the furnace, taken out and poured into an agate mortar for crushing to obtain LiMn 0.8 Fe 0.1 Zr 0.1 O2 two-phase cathode material.

[0254] A3, LiMn0.8 Fe 0.1 Zr 0.1 The X-ray diffraction pattern of O2 two-phase cathode material is shown in Figure 5 As shown. The diffraction peaks in the figure show that the products are o-LiMnO2 and DRX. The Fullprof software tool was used to refine and quantitatively analyze the composition content, and the proportion of ordered structure and disordered structure was calculated, among which the content of ordered structure o-LiMnO2 was 56.0%, and the content of disordered structure DRX was 44.0%.

[0255] Step 2: Assembling a lithium-ion battery based on a manganese-based ordered-disordered two-phase structure cathode material

[0256] Same as step 2 in Example 1.

[0257] Step 3: Testing of lithium-ion batteries based on manganese-based ordered-disordered two-phase structure positive electrode materials.

[0258] N1. The charge-discharge cycle performance of the assembled manganese-based ordered-disordered two-phase battery was tested using the Xinwei battery testing system (BTS Client 8.0.0.471). The test conditions were a current density of 20 mA g -1 , voltage range is 1.6-4.6V, temperature is room temperature 25℃. At a current density of 20mA g -1 The specific capacity is 165 mAh g at 20th -1 , at 100th, 157mAh g -1 , the capacity retention rate is 95.2%.

[0259] N2, as a comparison, the positive electrode material is replaced with olivine-type LiMn 0.8 Fe 0.1 Zr 0.1 The preparation process of O2 ordered layered single structure material is consistent with step 2 and step 3 of Example 1. The test results are: the current density is 20mA g -1 The specific capacity is 162 mAh g at 20th -1 , 142mAh g at 100th -1 . The capacity retention rate is 87.7%.

[0260] N3, as a comparison, the positive electrode material is replaced with LiMn 0.8 Fe 0.1 Zr 0.1 The preparation process of the O2 disordered rock salt single structure material is consistent with step 2 and step 3 of Example 1. The test results are: the current density is 20mA g -1 The specific capacity is 10 mAh g at 20th -1, at 100th the 9mAh g -1 The capacity retention rate was 90.0%.

[0261] Example 3: Preparation of LiMnO2-type two-phase manganese-based positive electrode material by molten salt method

[0262] Step 1: LiMn 0.8 Fe 0.1 Ti 0.1 Preparation of O2 two-phase structure cathode material

[0263] B1. Weigh 3.3550g Mn2O3, 0.3993g nano-TiO2, 0.3992g nano-Fe2O3, 1.9396g Li2CO3, 3.5249g lithium chloride and 2.3709g potassium chloride respectively, wherein the content of Li2CO3 added is 5wt% additionally added on the basis of the stoichiometric ratio to compensate for the loss of Li in the preparation process, the molar ratio of lithium chloride to potassium chloride is 6:4, and the mass ratio of the total mass of the lithium compound and the manganese compound to the mass ratio of the salt compound is 1:1.

[0264] After the above ingredients are prepared, 11.7916g of the prepared powder, 25g of stainless steel balls prepared according to the particle size and 25ml of anhydrous ethanol are poured into a ball mill with a capacity of 80mm in sequence, and the ball mill is placed and fixed on the ball mill for mixing. The ball mill is milled at a speed of 1000r / min on the ball mill for 4h. The mixed slurry is placed in a beaker and dried at 100℃ for 18h. The dried powder is ground with an agate mortar and sieved with a 200nm sieve to obtain a precursor powder with an average particle size of 100-200nm.

[0265] B2. Pour the dried powder into a corundum crucible and place it in a vacuum tube furnace. Heat treat it at 550°C for 10 hours in an argon atmosphere. The sample is cooled along with the furnace.

[0266] B3. After taking out, dissolve the molten salt compound in deionized water in an ultrasonic cleaner, filter, wash and dry at 110°C for 8h. After taking out, pour into an agate mortar and crush to obtain LiMn 0.8 Fe 0.1 Ti 0.1 O 22 Two-phase cathode material.

[0267] LiMn 0.8 Fe 0.1 Ti 0.1 The X-ray diffraction pattern of O2 two-phase cathode material is shown in Figure 6As shown. The diffraction peaks in the figure show that the products are o-LiMnO2, DRX and mixed phase m-LiMnO2. The Fullprof software tool was used to refine and quantitatively analyze the composition content, and the proportion of ordered structure and disordered structure was calculated. The content of ordered structure o-LiMnO2 was 53.3%, the content of disordered structure DRX was 40.1%, and the content of mixed phase m-LiMnO2 was 6.6%.

[0268] Step 2: Assembling a lithium-ion battery based on a manganese-based ordered-disordered two-phase structure cathode material

[0269] M1. Fully mix 350 mg of the conductive carbon black Super P obtained in step 1, 100 mg of the conductive carbon black Super P, and 1000 mg of a 5 wt% polyvinylidene fluoride solution. The 5 wt% polyvinylidene fluoride solution is prepared by fully mixing the polyvinylidene fluoride with the solvent N-methylpyrrolidone by magnetic stirring.

[0270] M2. The mixed slurry is coated on aluminum foil, dried in a vacuum oven at 80°C, and the dried product is cut by a cutting machine to obtain the positive electrode material.

[0271] M3. Assemble a manganese-based ordered-disordered two-phase battery in a glove box filled with argon atmosphere, using a CR2032 button cell, the positive electrode is the positive electrode material prepared in step M2, the electrolyte is LB-001 (1.0M LiPF6in EC:DMC=1:1Vol%), the separator is a polypropylene film (Celgard 2400), and the negative electrode is a lithium sheet.

[0272] M4. Assemble the negative electrode shell, lithium sheet, diaphragm, positive electrode, gasket, shrapnel and positive electrode shell in order, and press the above components into one in a button battery sealing machine to obtain a new manganese-based ordered-disordered two-phase battery.

[0273] Step 3: Testing of lithium-ion batteries based on manganese-based ordered-disordered two-phase structure cathode materials

[0274] N1. The charge-discharge cycle performance of the assembled manganese-based ordered-disordered two-phase battery was tested using the Xinwei battery testing system (BTS Client 8.0.0.471). The test conditions were a current density of 100 mA g -1 , voltage range is 1.6-4.8V, temperature is room temperature 25℃. At current density of 100mA g -1 The specific capacity is 140 mAh g at 20th -1 , at 100th, 137mAh g -1 , the capacity retention rate is 97.9%.

[0275] N2, as a comparison, the positive electrode material is replaced with ordinary olivine-type LiMn 0.8 Fe 0.1 Ti 0.1 The preparation process of O2 ordered material is consistent with step 2 and step 3 of Example 1. The test results are: the current density is 100mA g -1 The specific capacity is 124 mAh g at 20th -1 , 108mAh g at 100th -1 The capacity retention rate was 87.1%.

[0276] N3, as a comparison, the positive electrode material is replaced with ordinary LiMn 0.8 Fe 0.1 Ti 0.1 The preparation process of O2 disordered material is consistent with step 2 and step 3 of Example 1. The test results are: the current density is 100mA g -1 The specific capacity is 8 mAh g at 20th -1 , at 100th the 6mAh g -1 The capacity retention rate was 75.0%.

[0277] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A manganese-based positive electrode material having an ordered-disordered two-phase structure, characterized in that: The manganese-based positive electrode material is a two-phase mixture of an ordered structure phase and a disordered rock salt structure phase, wherein the content of the ordered structure phase is not less than 5%.

2. The manganese-based positive electrode material according to claim 1, characterized in that: The manganese-based positive electrode material is a LiMnO2-based ordered-disordered two-phase positive electrode material, and its molecular formula is Li 1+x Mn y M z O 2-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤1, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.

5.

3. The manganese-based positive electrode material according to claim 1, characterized in that: The manganese-based positive electrode material is a Li2MnO2-based ordered-disordered two-phase positive electrode material, and its molecular formula is Li 2-x Mn y M z O 2-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.

5.

4. The manganese-based positive electrode material according to claim 1, characterized in that: The manganese-based positive electrode material is a Li2MnO3-based ordered-disordered two-phase positive electrode material, and its molecular formula is Li 2-x Mn y M z O 3-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.

5.

5. The manganese-based positive electrode material according to claim 1, characterized in that: The manganese-based positive electrode material is a LiMn2O4-based ordered-disordered two-phase positive electrode material, and its molecular formula is Li 1+x Mn 2-y M z O 4-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0<y≤1, 0<z≤0.9, 0≤q≤0.

5.

6. The manganese-based positive electrode material according to claim 1, characterized in that: The manganese-based positive electrode material is a LiMnPO4-based ordered-disordered two-phase positive electrode material, and its molecular formula is Li 1+x Mn y M z PO 4-q N q , wherein M is one or more metal cations, N is one or more anions, 0≤x≤0.5, 0.1≤y<1, 0<z≤0.9, 0≤q≤0.

5.

7. The manganese-based positive electrode material according to any one of claims 2 to 6, characterized in that: The metal cation represented by M includes but is not limited to Ni 2+ ,Co 3+ , Fe 3+ ,Cr 3+ , Al 3+ , Ga 3+ ,In 3+ , Ti 4+ , Sn 4+ , Zr 4+ , Nb 5+ , Mo 6+ One or more of.

8. The manganese-based positive electrode material according to any one of claims 2 to 6, characterized in that: The anion represented by N includes but is not limited to F - , N 3- , Cl - , S 2- One or more of.